Workshop on the Impact of Digital Detox on Sleep Quality for a Better Lifestyle Health among University Students - Rizal Perlambang C NAWP (PT. Global Research Collaboration, 2025)
This community service project titled “Workshop: The Impact of Digital Detox on Sleep Quality for a Better Lifestyle Health Among University Students” aimed to enhance students’ awareness and behavioral management regarding responsible digital use and its relation to sleep quality. The program was implemented in two phases: a webinar workshop introducing the concept of digital detox and its physiological foundations, followed by Focus Group Discussions (FGDs) with pre-test and post-test assessments to evaluate behavioral changes. The workshop successfully improved participants’ digital health literacy and encouraged mindful technology practices. Quantitative analysis showed a 52.2% increase in overall knowledge scores and a 65.3% reduction in pre-sleep screen time. Moreover, the average sleep duration improved from 5.8 to 7.2 hours, and self-reported sleep quality rose by 53.7%. Qualitative reflections confirmed greater emotional stability, reduced anxiety, and higher concentration during academic tasks. The findings emphasize that digital detox education effectively bridges awareness and behavioral transformation by promoting self-regulation, reflection, and peer support. This initiative demonstrates the feasibility of integrating digital wellness programs into higher education as part of holistic student development. Sustainable replication of such initiatives can enhance mental resilience and foster balanced digital habits among Indonesia’s youth, aligning with global health goals for well-being and responsible technology use.